Evaluation of the policy options to adopt a water-energy-food nexus pattern by farmers: Application of optimization and agent-based models - Mirzaei, Abbas; Ashktorab, Niloofar; Noshad, Mohammad (Frontiers in Environmental Science, 2023)
In recent years, water-scarce regions (WSRs) have faced many challenges in order to achieve sustainable economic development. Sustainable economic development in the agricultural sector of WSRs is possible by paying attention to the water-energy-food nexus (WEFN) concept. WEFN determined using consumption, physical productivity, and economic productivity criteria of water and energy resources. According to the goals of physical and economic productivity of water and energy resources, it will be very difficult to implement WEF nexus patterns in WSRs with severe water resource crisis. The present study is aimed in WSRs to extract the resource allocation pattern based on the goals of the WEFN system using multi-criteria decision making (MCDM) tools and evaluate the cooperative behavior of farmers with this pattern under government's policy options using an agent-based model (ABM). The results for Doroodzan dam irrigation network as a WSR revealed that the pattern based on WEFN will lead to a 200 and 18 percent increase in physical and economic water productivity and a 156 and 67 percent increase in physical and economic energy productivity compared to the base pattern, but the implementation of this pattern requires 33% more water consumption. Therefore, it is very necessary to water resource management policies such as using modern irrigation technologies under government policy options in order to implement the pattern based on WEFN in WSRs. In this regard, the inflexibility of the government's policies will prevent the widespread implementation of the pattern based on WEFN and sustainable economic development at the regional level. Also, it can be concluded that the expansion of sustainable patterns in the agricultural sector will not be possible without considering the situation of the region from the point of view of water resources and also the cooperative behavior of the farmers. Finally, the framework of the present study is recommended to achieve the goals of sustainable economic development of the agricultural sector in WSRs.